A Survey of the Nutritional Status of Women at Otinibi, a Peri-Urban Community near Accra - Banson, R. (University of Ghana, 2000)
The purpose of this study was to assess the effects of women’s life circumstances on their health and nutritional status. The study included women of reproductive age (15 - 45 years old) and 74 women took part in the study. Study-specific semi-structured questionnaires were used to collect dietary, socioeconomic, demographic and workload data. Urinary and random blood glucose determinations were used to test for the prevalence of diabetes mellitus. The subjects had mean ( } SD) random blood glucose concentration of 87.01 } 11.45ug/dL. None was identified to have diabetes mellitus. Blood haemoglobin and serum iron determinations were used to test for anaemia. The mean ( } SD) blood haemoglobin and serum iron concentrations were respectively 11.41 } 1.26 g/dL and 58.41 } 19.22 |_ig/dL. About 60 % of the subjects were found anaemic. Protein and vitamin A status were also assessed. The average serum total protein was 9.14 } 0.97 g/dL, mean serum albumin was 4.372 } 6.400 g/dL and that of serum retinol, 33.79 ± 9.74 p,g/dL. None of the subjects was found to be protein deficient and the prevalence of subclinical vitamin A deficiency was about 11%. Body mass index (BMI) for each subject was computed from the height and weight measurements taken. The BMI values had a mean (+ SD) of 22.492 } 4.100 kg/m2. Prevalence of underweight and obesity were 5% and 8% respectively. Waist - hip ratios (WHR) were calculated from the measurements of waist and hip circumferences. The mean ( } SD) WHR was 0.859 } 0.057. About 49% of the subjects had WHR values > 0.85, indicating a risk of suffering from chronic diseases such as diabetes mellitus and hypertension. The systolic and diastolic blood pressures of subjects were measured with an electronic sphygmomanometer. The mean values for the systolic and diastolic blood pressures were respectively 109.635+ 11.355mmHg and 70.000 } 8.365 mmHg. The prevalence of low blood pressure was 3% - 18% and that of high blood pressure was about 1% - 5%. The waist-hip ratio showed significant positive correlation with income (r = 0.35), diastolic blood pressure (r = 0.32), systolic blood pressure (0.22) body mass index (r = 0.32) and inverse correlation with education (r = -0.33). The body mass index showed an association with serum retinol concentration (r = 0.41), systolic blood pressure (r = 0.53), diastolic blood pressure (r = 0.45), and education (r = -0.12). Blood haemoglobin concentration also showed positive correlation with serum iron concentration (r = 0.81) and education (r = 0.12). Serum albumin correlated significantly with serum total proteins (r = 0.81). From the main findings of this study, it could be concluded that with the exception of the serum iron and blood haemoglobin statuses, the nutritional status of the women of childbearing age were generally good. The waist-hip ratio and body mass index measurements also indicated their nutritional status to be good. Improving the level of education attained, and improving on the fanning practice systems of the women would go a long way to enhance their nutrition and health status.
Thesis(MPhil) - University of Ghana, 2000